2019
DOI: 10.1111/vde.12731
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological findings and clinical outcomes in 49 cases of feline pemphigus foliaceus examined in Northern California, USA (1987–2017)

Abstract: Background -Few studies have described the pathophysiology, clinical course, treatment outcomes and quality of life (QoL) of cats with pemphigus foliaceus (PF). Objective -Describe clinicopathological features, treatment outcomes and impacts on QoL in feline PF.Animals -Forty-nine client-owned cats with PF that presented to a veterinary teaching hospital between 1987 and 2017.Methods and materials -Medical records and histopathological reports were reviewed to obtain clinicopathological data and treatment outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 21 publications
1
23
1
Order By: Relevance
“…15 Though 80-92% of cats with PF have pinnal lesions, the ear canal is less frequently affected. [61][62][63] Otitis externa has been reported in 7-30% of cats with PF. 63,64 Most cats with PF have lesions affecting multiple sites.…”
Section: Pemphigus Foliaceusmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Though 80-92% of cats with PF have pinnal lesions, the ear canal is less frequently affected. [61][62][63] Otitis externa has been reported in 7-30% of cats with PF. 63,64 Most cats with PF have lesions affecting multiple sites.…”
Section: Pemphigus Foliaceusmentioning
confidence: 99%
“…[61][62][63] Otitis externa has been reported in 7-30% of cats with PF. 63,64 Most cats with PF have lesions affecting multiple sites. [61][62][63] The primary lesion of PF is a subcorneal pustule, but these are prone to rupture, so crusts, erosions, alopecia and erythema are more often seen clinically.…”
Section: Pemphigus Foliaceusmentioning
confidence: 99%
“…Pemphigus foliaceus is another disease of this group. Here, pruritus occurs in more than half of the patients (61%) (54). The histopathological characteristic findings include intraepithelial cleavage with acantholysis beneath the stratum corneum and a dermal inflammation, predominantly with neutrophils, mast cells and plasma cells (54).…”
Section: Pemphigus Groupmentioning
confidence: 99%
“…Here, pruritus occurs in more than half of the patients (61%) (54). The histopathological characteristic findings include intraepithelial cleavage with acantholysis beneath the stratum corneum and a dermal inflammation, predominantly with neutrophils, mast cells and plasma cells (54). Although there is little systematic data on pruritus in the pemphigus group, the parameter pruritus contributes to the assessment whether the disease is controlled or not (55).…”
Section: Pemphigus Groupmentioning
confidence: 99%
“…2,3 The clinical and therapeutic aspects of feline PF have been extensively reviewed and updated, yet investigations into an underlying pathogenesis remain minimal. 2,[4][5][6][7] As feline PF is phenotypically and histologically similar to the canine and human forms, an aetiology involving pathogenic autoantibodies targeting keratinocyte adhesion protein(s) can be inferred. 2 Prior direct immunofluorescence (IF) studies that successfully confirmed circulating, anti-keratinocyte autoantibodies in biopsies from PF-affected cats support this hypothesis.…”
Section: Introductionmentioning
confidence: 99%